Models of Integrating Religion and Science in Islamic Religious Education Learning - Ramadina, Evy; Naim, Ngainun; Akhyak, Akhyak (IJoIS: Indonesian Journal of Islamic Studies, 2025)
The relationship between religion and science in Islamic education has developed as a response to the longstanding dichotomy between religious knowledge and general (secular) sciences, a division that has shaped educational structures and societal mindsets and produced an enduring epistemological gap. This study aims to analyze and categorize the dominant paradigms governing the relationship between religion and science and to examine their implications for Islamic Religious Education (PAI). Using a qualitative literature review, the study analyzes books and peer-reviewed journals addressing religion–science relations through the analytical framework of Miles, Huberman, and Saldaña, encompassing data condensation, data display, and conclusion drawing. The findings identify four principal paradigms in religion–science relations: conflict, independence, dialogue, and integration. Among these, the integrative paradigm is regarded as the most comprehensive, as it seeks to reconcile empirical inquiry with transcendental values while respecting their distinct epistemological foundations. Within PAI learning, this paradigm is reflected in curriculum design, interdisciplinary pedagogical approaches, and the incorporation of spiritual and ethical values into science-related instruction. The novelty of this study lies in its systematic synthesis of philosophical paradigms of religion–science relations with their pedagogical application in the Indonesian Islamic higher education context, particularly within UIN, IAIN, and STAIN. The study concludes that relating religion and science is not merely an academic project but also a cultural and spiritual process that supports a holistic understanding of reality and promotes Islamic education that remains responsive to contemporary challenges.